The Effect of Defaunating Agents Supplementation and Time of Incubation on The In Vitro Dry Matter, Organic Matter Degradability and Products of Fermentation - putra, S (ANIMAL PRODUCTION, 2006)
In Vitro experiment was conducted  to study  the effect of  defaunating agents supplementation and time of incubation  on the dry matter, organic matter degradability and products of fermentation.  A completely randomized design with split in time arrangement (4 x 5) on two replicates was used in this experiment.  The first (main) factor was time of incubation (1.5, 3,0 and 4.5 hours respectively) and the second factor was no supplement of defaunating agent ( A, as  a control),  a supplement of 10% Hibiscus tilliaceus leaves (B), a supplement of 10% Hibiscus rosasinensis leaves (C), a supplement of 2% corn oil (D), and a supplement of 2% coconut oil (E). Results of the experiment indicated that treatment C increased 10.66% DM degradability which were significantly different (P<0.03) than treatment A, while DM degradability on treatment B, D, and E were increased 4.29, 5.58, 6.24% than treatment A, respectively but it were not significantly different.  Defaunating agents supplementation (treatment B, C, D, and E) increased 8.59, 15.19, 9.62, and 8.01% OM degradability, respectively (P<0.03)  than without supplementation (A), but between defaunating agents supplementation were not significantly different. DM degradability during incubation (1.5 to 4.5 hours)  were significant different statistically (P<0.04) which the highest was on 4.5 hour incubation, while OM degradablity during incubation were not significantly different.  Total VFA  on the defaunating agents supplementation and during time of incubation were significantly different which the highest were on the Hibiscus rosasinensis supplementation (C) and on  the 4.5 hours incubation,  respectively. N-ammonia on the defaunating agents supplementation and during incubation were not significantly different (P>0.05) which the highest were on the Hibiscus rosasinensis supplementation (C) and on the 3.0 hours incubation, respectively.  It was concluded that defaunating agents were affected significantly different on the DM and OM degradability and total VFA, but were not affected on the N-ammonia.  Time of incubation from 1.5 to 4.5 hours increased DM, OM degradability and total VFA, but N-ammonia was decreased. Hibiscus rosasinensis was the best defaunating agents, particularly it was increased DM, OM degradability, total VFA and N-ammonia, absolutely.  (Animal Production 8(2): 121-130 (2006) Key Words: Defaunating agents, Time of incubation, DM and OM Degradability, Products of fermentation